Re-discussion of the importance of ionic interactions in stabilizing ligand-opioid receptor complex and in activating signal transduction - Gentilucci, Luca; Squassabia, Federico; Artali, Roberto (Current drug targets, 2007)
Among the many receptor classes of the GPCR family, ORs constitute a privileged drug target for their involvement in pain modulation and in a number of physiological functions and behavioural effects. Endogenous and exogenous opioid agonists have been the subject of intense investigations aiming to develop safe and potent analgesics for clinical practice; however, despite the large number of highly selective opioid agonists so far discovered, there is no convincing alternative to the use of morphine, fentanyls, and their derivatives. Alternative compounds could be very useful for treating pain forms "resistant" to the usual therapeutic agents. The recent discovery of a small number of atypical opioid agonists can furnish promising candidates for the development of alternative analgesic. In particular, a few molecules exist that can bind and activate ORs even deprived of the "minimal pharmacological requisites" generally considered to be necessary. In these cases it appears that receptor activation must be based on different ligand-receptor interaction mechanisms. Taken together, the data discussed in the review suggest that the prevailing assumptions about OR binding need revision. In particular, they strengthen the evidence that ORs can bind ligands via diverse binding modes, and in some cases an electrostatic interaction is not an absolute requirement.